Selection of host differentials for the identification of Albugo candida pathotypes - A.K. TEWARI, PUJA PANDEY* and (Indian Phytopathology, 2017)
Albugo candida (A. cruciferum) the cause of the white rust/white blister of the rapeseed and mustard occurs in all cruciferous growing countries. The present investigation was conducted to study disease reaction on different Brassica genotypes viz., EC-399301, NRCDR-513, EC-399296, Rohini, EC-399299, NRCDR-515, BIOYSR, EC-399313, JM-1 (B. juncea), EC-414293 (B. rapa), GSL-1 (B. napus), PBC -9221 (B. carinata) and B. nigra local during year 2010-11 and Rohini, EC-399299, EC-414293, B. nigra local, EC-399296, EC-399313, EC-399301, JM-1, PBC-9221, NRCDR-515, GSL-1 using different A. candida isolates (Pantnagar, Ludhiana, Hisar, Bharatpur and Delhi) for the selection of host differentials and identification of A. candida pathotypes. Based on phenotypic disease reactions at cotyledonary and true leaf stage, the Brassica genotypes were grouped into a set of five host differentials. Among various disease management practices, breeding for resistant genotype/varieties is one of the most ecofriendly, economic and effective method for the management of plant diseases.